Relation Between Adolescent Cardiovascular Risk Factors and Carotid Intima‐Media Echogenicity in Healthy Young Adults: The Atherosclerosis Risk in Young Adults (ARYA) Study - Anouk L. M. Eikendal; Karlijn A. Groenewegen; Michiel L. Bots; Sanne A. E. Peters; Cuno S. P. M. Uiterwaal; Hester M. den Ruijter (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundEchogenicity is an ultrasound measure that reflects arterial wall composition. In adult populations, lower carotid intima‐media echogenicity relates to an unfavorable cardiovascular risk burden yet appears to reflect a different aspect of arterial wall remodeling than carotid intima‐media thickness (CIMT). Since studies on carotid intima‐media echogenicity earlier in life are lacking, we investigated associations between adolescent cardiovascular risk factors and young adulthood carotid intima‐media echogenicity and compared this to CIMT. Methods and ResultsIn 736 participants of the Atherosclerosis Risk in Young Adults study, information on adolescent anthropometrics, puberty stage, and systolic blood pressure (SBP) was available. In young adulthood, demographics, anthropometrics, and fasting plasma samples were collected. Common CIMT and echogenicity, quantified as gray‐scale median (GSM), were evaluated using B‐mode ultrasonography. Lower and higher GSM values, respectively, represented lower and higher echogenicity. Associations of adolescent body mass index and SBP with young adulthood GSM and CIMT were evaluated using linear regression analysis. Mean age was 13.5 years in adolescence and 28.4 years in young adulthood (difference: 14.9 years). After full adjustment, adolescent body mass index related to GSM (β=−1.62/SD; 95% CI: −2.79, −0.46; P=0.006), independent of CIMT. Adolescent SBP did not relate to GSM. Moreover, adolescent body mass index (β=8.06 μm/SD [95% CI: 4.12, 11.99], P<0.001) and SBP (β=4.69 μm/SD [95% CI: 0.84, 8.54], P=0.02) related to CIMT. ConclusionsAdolescent body mass index related to GSM and CIMT in young adulthood; SBP only related to CIMT. Hence, carotid intima‐media echogenicity appears to be involved in arterial wall remodeling, yet may mimic a different facet of this process than CIMT.